PREVALENCE OF METABOLIC SYNDROME IN WOMEN OFDIFFERENT AGE GROUPS IN RURAL POPULATION OF ANDHRAPRADESH (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Background & Objectives: The main objective of the study is to identify the prevalence of Metabolic syndrome as peoplewith the Metabolic syndrome are at increased risk for developing diabetes mellitus, cardiovascular disease as well asincreased mortality from cardiovascular disease risk factors.Materials & Methods: A total number of 60 female subjects participated in the study. The subjects were grouped into twodifferent age groups i.e. 30-40 and 40-50 years age. The study was approved by the Institutional Ethics Committee. Lipidprofile, Fasting blood glucose, Blood pressure, Height, Weight & Waist circumference were recorded in all the subjects.Results: We observed that the prevalence of metabolic syndrome was 20% in women of 30-40 age group and 63.33% inwomen of 40-50 years of age group based on the NCEP ATP-III criteria.Conclusion: Programs aimed at detection and treatment of dyslipidemia, hypertension, diabetes, and obesity may reducethe burden of Metabolic syndrome in our population. Metabolic Syndrome present in epidemic proportions among theelderly represents one of the major threats to longevity and healthy aging.